Malawi and Scotland : together in the talking place since 1859 - Ross, Kenneth R. (Mzuni books ;, 2013)
This book tells the story of the remarkably enduring bonds between Malawi and Scotland - from the time of David Livingstone to the flourishing cultural, economic and religious relationships of the twenty-first century. Why should there be any significant relationship between one small nation on Europe's north-western seaboard and another in the interior of Africa? How did it reach the stage where in 2012 Fiona Hyslop, Cabinet Secretary for Culture and External Affairs in the Scottish Government, could describe Malawi as Scotland's "sister nation"? This book aims at answering these questions.